2014
DOI: 10.1016/j.vaccine.2013.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species protection: Schistosoma mansoni Sm-p80 vaccine confers protection against Schistosoma haematobium in hamsters and baboons

Abstract: The ability of the Schistosoma mansoni antigen, Sm-p80, to provide cross-species protection against Schistosoma haematobium challenge was evaluated in hamster and baboon models. Pronounced reduction in worm burden (48%) and in tissue load (64%) was observed in hamsters vaccinated with recombinant Sm-p80 admixed with Glucopyranosyl Lipid Adjuvant-Stable Emulsion (GLA-SE). Similarly, in baboons, the Sm-p80 / GLA-SE vaccine produced a 25% reduction in S. haematobium adult worms and decreased the egg load in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 45 publications
(76 reference statements)
4
46
0
Order By: Relevance
“…Over the last two decade, we have employed a systematic approach to developing Sm-p80-based vaccine for schistosomiasis control. Several studies by our group using various Sm-p80-based vaccination strategies have demonstrated high levels of prophylactic and therapeutic efficacy against S. mansoni infections in both mice and baboons (Ahmad et al 2009a; Ahmad et al 2009b; Ahmad et al 2009c; Karmakar et al 2014a; Karmakar et al 2014b; Le et al 2014; Zhang et al 2010b; Zhang et al 2011); efficacy levels obtained with Sm-p80 vaccine are comparable to previously obtained data with S. mansoni radiation attenuated (RA) cercariae vaccine, which is a gold standard for anti-schistosome protective immunity. Immunizations with the RA vaccine have been demonstrated to show significant protection levels ranging from 56% to as high as 80% following cercariae challenge (Anderson et al 1999; Ganley-Leal et al 2005; Sher et al 1982; Wilson et al 1999).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Over the last two decade, we have employed a systematic approach to developing Sm-p80-based vaccine for schistosomiasis control. Several studies by our group using various Sm-p80-based vaccination strategies have demonstrated high levels of prophylactic and therapeutic efficacy against S. mansoni infections in both mice and baboons (Ahmad et al 2009a; Ahmad et al 2009b; Ahmad et al 2009c; Karmakar et al 2014a; Karmakar et al 2014b; Le et al 2014; Zhang et al 2010b; Zhang et al 2011); efficacy levels obtained with Sm-p80 vaccine are comparable to previously obtained data with S. mansoni radiation attenuated (RA) cercariae vaccine, which is a gold standard for anti-schistosome protective immunity. Immunizations with the RA vaccine have been demonstrated to show significant protection levels ranging from 56% to as high as 80% following cercariae challenge (Anderson et al 1999; Ganley-Leal et al 2005; Sher et al 1982; Wilson et al 1999).…”
Section: Discussionsupporting
confidence: 76%
“…Immunizations with the RA vaccine have been demonstrated to show significant protection levels ranging from 56% to as high as 80% following cercariae challenge (Anderson et al 1999; Ganley-Leal et al 2005; Sher et al 1982; Wilson et al 1999). Based on the findings from our recent study which evaluated the cross-species protective efficacy of Sm-p80-based vaccine against urinary schistosomiasis in hamsters and baboons in which Sm-p80 vaccine offered significant protection against S. haematobium infections (Karmakar et al 2014a), we hypothesized that protection against Asiatic schistosomiasis caused by S. japonicum infections would be possible by inducing specific host immune responses through Sm-p80-based vaccination. The data presented here from the two independent S. japonicum vaccine trials showed that Sm-p80 vaccine conferred significant cross-species protection against Asiatic schistosomiasis in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLA adjuvant formulations have been used with experimental vaccines for influenza, HIV (29), respiratory syncytial virus (RSV) (30), leishmaniasis (31), malaria (32), and leprosy (33) in addition to TB (34,35). Many of these vaccines using GLA formulations have also resulted in protection in preclinical animal models, including mice (34)(35)(36), ferrets (37,38), guinea pigs (34,35,39), cotton rats (30), and hamsters (40), against infectious challenge.…”
Section: Et Al Have Shown a Transient Increase In Ifn-␥ From Cd4mentioning
confidence: 99%
“…These levels of protection have previously never been seen with a schistosome antigen in large animal models. Furthermore, in addition to prophylactic efficiency, the Sm-p80 immunizations could also induce killing of established adult worms and protect against urinary schistosomiasis caused by S. haematobium28 .…”
mentioning
confidence: 99%